PENGARUH CORPORATE GOVERNANCE, AUDITOR EKSTERNAL, DAN UKURAN PERUSAHAAN TERHADAP INTEGRITAS LAPORAN KEUANGAN - Radea Dian Purnama, 11.05.52.0034; Srimindarti, Ceacilia (Students Journal of Accounting and Banking, 2016)
This study aims to examine and analyze corporate governance, external auditors, and the size of the company for the integrity of the financial statements listed in GCPI. The population in this study is a population used in this study is a company registered in the Corporate Governance Forum Indonesia (FCGI) in 2010-2014. This study using the technique of purposive sampling in the sampling. The analysis was performed by multiple regression using SPSS for windows version 19:00. The results showed that corporate governance is not significant positive effect on the integrity of financial statements. External Auditor significant negative effect on the integrity of financial statements. Size companies significant negative effect on the integrity of financial statements. Â Keywords: Corporate Governance, External Auditors, Company Size, Integrity of Financial Statements